The Existence of Prophetic Learning in Improving Spiritual Intelligence Through Tahfidz Al-Qur’an for Students - Nicky Estu Putu Muchtar; Wahyuni Ahadiyah; Evi Zulianah; Siti Khodijah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This study was aimed at determining the existence of prophetic learning to improve spiritual intelligence through the tahfidz Al-Qur’an program for grade 8 students at SMPN 1 Deket Lamongan. The method applied was a qualitative method with a natural setting, where the researcher conducted research in the field naturally which then produced several findings. First, the existence of prophetic learning included the values ​​of humanization, liberation, and transcendence, which was the implementation of attitudes to solve students’ moral degradation problem. Second, fostering spiritual intelligence by embedding prophetic characters through memorizing Al-Qur’an. Third, the tahfidzul Qur’an process program used talqin, tasmi’ and muroja’ah methods. Fourth, supporting factors included: competent teachers in the field of tahfidz Al-Qur’an, adequate facilities and infrastructure, motivational support and appreciation from all stakeholders in the school environment and tahfidz graduation. Inhibiting factors included; there were students that were unable to read Al-Qur’an, some never recite at home, some were lack motivation from parents and students’ lack of concentration because they often play online games. Novelty was also found that one of the students was classified as an inclusive student, so the approach in the tahfidz Al-Qur’an program was different from other students. Tahfidz teachers at SMPN 1 Deket never discriminated against their students. Inclusive students needed special attention and approach to repeat their memorization. From the experience of teachers who taught were by using methods of Tikrarul Mahfudz, Kitabul Mahfudz, and Isati’amul Mahfudz methods.